2022
DOI: 10.1016/j.ebiom.2021.103783
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights in ascending aortic size and distensibility

Abstract: Summary Background Alterations in the anatomic and biomechanical properties of the ascending aorta (AAo) can give rise to various vascular pathologies. The aim of the current study is to gain additional insights in the biology of the AAo size and function. Methods We developed an AI based analysis pipeline for the segmentation of the AAo, and the extraction of AAO parameters. We then performed genome-wide association studies of AAo maximum area, AAo minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 89 publications
6
26
1
Order By: Relevance
“…In agreement with previous studies, our measurements were significantly larger in men than women, 10,17,18 with increased aortic diameter in men suggested as a reason for the greater incidence of AAA in men. 19 We found that CSA IDPs increased with advancing age, in both men and women.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies, our measurements were significantly larger in men than women, 10,17,18 with increased aortic diameter in men suggested as a reason for the greater incidence of AAA in men. 19 We found that CSA IDPs increased with advancing age, in both men and women.…”
Section: Discussionsupporting
confidence: 93%
“…The strongest association was observed for the thoracic descending aorta, which is perhaps to be expected since this measurement closely corresponds to the location of CMR measurements of the ascending and descending aorta. 10 In agreement with previous studies, our measurements were significantly larger in men than women, 10,17,18 with increased aortic diameter in men suggested as a reason for the greater incidence of AAA in men. 19 We found that CSA IDPs increased with advancing age, in both men and women.…”
Section: Discussionsupporting
confidence: 92%
“…We compared our association results for aortic areas with those reported for aortic diameters in recent papers and preprints 30 – 32 based on the same UK Biobank imaging data set, but using different methods and metrics for aortic dimensions (see Supplementary Data 11 ). We replicated 75 of the previously reported genome-wide significant association loci and added associations for clinically relevant phenotypes (ascending and descending aortic distensibility) to identify a further 27 novel associations.…”
Section: Resultsmentioning
confidence: 99%
“…Although genetic variation in TBX20 has been associated with a spectrum of congenital cardiac lesions relating to cardiac and vascular development, 75 there have been increasing observations that genetic loci near TBX20 meet genome wide significance for disease in adulthood including coronary artery disease, 76 myocardial infarction, 77 blood pressure, 78 and aortic dimension and distensibility. 17, 79 Similarly, variants near GATA4 and members of the HOXB family of transcription factors such as HOXB7 have been associated with hypertension, 80, 81 while HAND2 variants are associated with aortic dimension and atrial fibrillation. 17, 82 The vascular bed and cell type specific chromatin accessibility observed in our study of these developmental transcription factors may suggest their ongoing role in mediating vascular disease in adulthood in a vascular bed specific mechanism.…”
Section: Discussionmentioning
confidence: 99%